The benefits of information system of water pollution at Bedadung river towards oral and dental health of the community - Heru Ernanda; Zahreni Hamzah; Dyah I. Setyowati; Ary TW. Handayani; Tecky Indriana (DiscoverSys Inc., 2018)
Objective: The purpose of creating the river water pollution information systems related to oral and dental health community is to facilitate the analysis of diseases caused by water pollution.Material and Methods: The Environment-based Health Management Information System based on GIS is based on real data of Bedadung River-Jember Regency, East Java, Indonesia includes the location of the dumping points, photo dumping points, the area of garbage accumulation, and tooth and mouth disorders that arise due to contamination of river water, which is associated with community dental and oral health data that taken by survey.Results: Through the Environmental Health Information System information can be displayed about the environment and the dental and oral status of the population around the Bedadung river.Conclusion: The use of the Environment-Based Health Management Information System is very important to help support the government's decision to prevent the spread and severity of community diseases caused by river water pollution, reduce morbidity and mortality, and reduce the burden of government financing to treat diseases and disability integrated in an integrated manner.